2023
DOI: 10.3390/pr11072076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Properties on Filter Cake Compaction Behavior under Oscillatory Shear

Tolga Yildiz,
Joel Gegenheimer,
Marco Gleiß
et al.

Abstract: Filter cake compaction is a common method for mechanical deliquoring of compressible filter cakes. In addition to the conventional squeezing compaction method, applying oscillatory shear to filter cakes at low pressure is an alternative compaction process in cake filtration. While basic differences in terms of compaction success have already been identified for various materials, a systematic analysis of the influence of material properties on compaction behavior under oscillatory shear is missing. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Due to the widely distributed particle size, this material tends to show particle segregation during cake formation for small solid volume fractions of the slurry. Following Yildiz et al [36], who reported correlations between the mean particle size and particle size distribution width of ground calcium carbonates and the vibration compaction behavior, the material is expected to be compressible by oscillatory shear. For these reasons, the choice of this material as a model particle material for this study was justified.…”
Section: Model Particle Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the widely distributed particle size, this material tends to show particle segregation during cake formation for small solid volume fractions of the slurry. Following Yildiz et al [36], who reported correlations between the mean particle size and particle size distribution width of ground calcium carbonates and the vibration compaction behavior, the material is expected to be compressible by oscillatory shear. For these reasons, the choice of this material as a model particle material for this study was justified.…”
Section: Model Particle Materialsmentioning
confidence: 99%
“…The cake residual moisture dropped rapidly until the vibration application no longer removed any more liquid from the cake after a few number of oscillations n, and a stationary equilibrium value was reached. The model in Equation ( 6), already used by Illies et al [30,31] and Yildiz et al [36] to describe the exponential kinetics of vibration compaction, provides the minimum achievable residual moisture RM ∞ at a certain frequency in the compaction equilibrium by approximating the experimental data. Other fitting parameters include the consolidation potential B and the compaction rate ϑ.…”
Section: Compaction and Dewatering Of Homogeneous And Segregated Filt...mentioning
confidence: 99%
See 1 more Smart Citation